GAYA DAN STRATEGI BELAJAR SISWA DALAM PROSES PEMBELAJARAN BAHASA INDONESIA - Husada, Lukas Budi (Jurnal Pena Indonesia, 2019)
Every student has different potentials and characteristics. The difference in character of each student is related to the ability of different brains to absorb, process, and convey information to others. These characters are closely related to student learning styles and how to learn the right strategies so that they can easily understand Indonesian language concepts and skills. In general, learning styles have four styles abbreviated as VARK, namely 1) visual, 2) auditive, 3) read / write, and 4) kinesthetic. While there are 3 types of learning strategies, namely 1) cognitive strategies, 2) meta-cognitive strategies, and 3) social-affective strategies. Based on the different learning styles of each student, the teacher can determine suitable or appropriate learning strategies. Thus, the implementation of Indonesian language learning is expected to encourage students to learn according to their interests. Therefore, knowing the style and learning strategies of students can be a guide that is able to optimize the learning process of Indonesian